Exploration And Characterization Of Fungi From Oil Palm Rhizosphere (Elaeis Guneensis Jacq) On People's Plantations In Kuantan Singingi Regency - Desta Andriani; Deno Okalia; Seprido Seprido (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
The rhizosphere is an excellent habitat for microbial growth because plant roots provide a variety of organic materials that generally stimulate microbial growth. This study aimed to explore and determine the character of fungi from oil palm rhizosphere (Elaeis guneensis Jacq) on smallholder plantations in Kuantan Singingi Regency. This research was conducted at the Islamic University of Kuantan Singingi. The method used was an experimental method carried out in two stages. The first stage was a random sampling survey. The sample was then taken to the Basic Laboratory of the Faculty of Agriculture, Kuantan Singingi Islamic University for analysis. They are Singingi Hilir District, Kuantan Mudik District, Kuantan Tengah District, Benai District, Pangean District and Sintajo Raya District. The most isolates were found in Singingi Hilir sub-district, the plant age was 2 years and the fertile soil was blackish brown. The least number of isolates was found at the age of 10 years, even though the soil was fertile. The age of the plant affected the microbial activity in the rhizosphere. The older the plant the microbial activity decreased. Therefore, it caused the number of isolates found to be small. Characteristics of isolates isolated at a younger plant age were more varied in color.